Strategic management competitiveness & globalization : concepts and cases - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E.; Harrison, Jeffrey S. (Cengage Learning, 2024)
Written by prominent management scholars and award-winning instructors, Hitt/Ireland/Hoskisson/Harrison's STRATEGIC MANAGEMENT: COMPETITIVENESS AND GLOBALIZATION, 14E provides an intellectually rich, yet practical, analysis of strategic management with updates, new research citations and twenty new cases.